The effects of supply chain concentration on working capital management, firm performance and bankruptcy risk: Empirical evidence from China's automobile manufacturing industry - Luo, Nachuan (2022)
The purpose of this dissertation is to explore the effects of supply chain concentration in the Chinese automobile manufacturing industry. Past literature has mainly examined the effect of customer concentration from the perspective of firm performance, but rarely from the perspective of working capital management and bankruptcy risk. As a result, this dissertation applies an empirical analysis to investigate the effects of supplier concentration and customer concentration on working capital management, firm performance and bankruptcy risk and the effect of working capital management on firm performance.